Coopetition in internationalization of wineries in Southern Brazil with the support of formal institutions - Monticelli, Jefferson Marlon; Vasconcellos, Silvio Luís de; Garrido, Ivan Lapuente (Revista de Administração da UFSM, 2019)
This study analyses the coopetition strategy adopted by wineries in Southern Brazil with the support of local formal institutions to promote their internationalization. A multiple case study with 21 interviews with wineries and formal institutions of the industry was carried out. We used the discourse analysis based on the following categories: industry characterization, national and international markets, internationalization process, and institutional environment. The interpretations regarding the Integrated Sectorial Project (ISP) Wines of Brasil are shown. Despite its relevance, not all those involved have joined the project, because it promotes the internationalization unevenly through the competitive advantage while enhancing the differences between the wineries. The main contributions are expanding the knowledge about coopetition by understanding the role of formal institutions and promoting the international competitiveness of firms in the wine industry.